Measuring hunger - Fritschel, Heidi; Hallowell, Carolyn; Chu, Adrienne; Gustafson, Sara; Heard, Josh; MacNeil, Marcia; McMullan, Sarah; Shelton, Peter; Sullivan, Rebecca Harris; Kiener, Robert; Weeks, Jennifer (International Food Policy Research Institute, 2013)
A central part of IFPRI’s mission is to provide policy solutions for ending hunger and malnutrition. This mission implies that we know the size and scope of the hunger problem around the world. In fact, however, measuring hunger is fraught with difficulties. Do we simply count the calories available to a person or a household? How should we account for people who consume enough calories but too few vitamins and minerals? Some people require more calories and micronutrients because they are highly active or pregnant. How do we count them? What are the advantages and disadvantages of measuring hunger on a national scale compared with a household or individual scale? These are some of the thorny questions addressed in the feature article of this issue of INSIGHTS, which also describes other important research happening at IFPRI.